2004
DOI: 10.1074/jbc.m308819200
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characterization of the Entire Bacterial Surface Layer Protein SbsB and Its Two Distinct Functional Domains

Abstract: The crystalline bacterial cell surface layer (S-layer) protein SbsB of Geobacillus stearothermophilus PV72/p2 was dissected into an N-terminal part defined by the three consecutive S-layer homologous motifs and the remaining large C-terminal part. Both parts of the mature protein were produced as separate recombinant proteins (rSbsB 1-178 and rSbsB ) and compared with the full-length form rSbsB 1-889 (rSbsB). Evidence for functional and structural integrity of the two truncated forms was provided by optical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 44 publications
2
41
0
Order By: Relevance
“…7,[18][19][20] The self-assembly process of monomeric S-layer proteins to two-dimensional protein crystals has been studied using chemical cross-linking 21 and AFM. 10 The proteins' ability to self-assemble is usually localized within one or more crystallization domains, which can be dissected from the cell-wall anchoring domain, as shown by genetic or proteolytic truncation experiments 1,[22][23][24][25][26] and supported by insertion mutagenesis studies. 26,27 Relatively little is known about the molecular nature of the interactions between S-layer subunits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,[18][19][20] The self-assembly process of monomeric S-layer proteins to two-dimensional protein crystals has been studied using chemical cross-linking 21 and AFM. 10 The proteins' ability to self-assemble is usually localized within one or more crystallization domains, which can be dissected from the cell-wall anchoring domain, as shown by genetic or proteolytic truncation experiments 1,[22][23][24][25][26] and supported by insertion mutagenesis studies. 26,27 Relatively little is known about the molecular nature of the interactions between S-layer subunits.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the pores are round and small with an internal diameter of 1 nm and two are larger and oval shaped with dimensions of 3.5 nm × 1.5 nm. The propensity for assembly resides in the C-terminal 712-aminoacid-long crystallization domain of SbsB, 22 while the N-terminal anchoring domain (residues 32 to 208) binds to a secondary cell wall polymer (SCWP) that is covalently linked to the peptidoglycan sacculus within the cell wall. 32 In the previous study, a chemical approach was used to investigate the structure of SbsB.…”
Section: Introductionmentioning
confidence: 99%
“…SbsB is expected to consist of fibronectin type III and Ig-like domains, structures of known mechanical stability, which allows for the assumption that the double peak originates from the unfolding of such domains in the protein. Thermally and chemically induced unfolding studies also indicated that SbsB is a multidomain protein exhibiting a complex unfolding behavior, with a three-step unfolding having been observed (16). A contour length increase of about 12 nm indicates that the consecutive unfolding intermediates are closely located in the structure of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…This specific molecular interaction is often mediated by a recurring structural motif of approximately 55 amino acids, which is mostly found in triplicate at the N-terminus of S-layer proteins. These so-called SLH motifs are involved in cell wall anchoring of S-layer proteins by recognizing a distinct type of SCWP which carries pyruvic acid residues [32,112,[136][137][138][139][140]. Moreover, the coexistence of two N-terminally located binding domains for SCWPs and peptidoglycans was also described for the SLH domain carrying S-layer protein of G. stearothermophilus PV72/p2 (SbsB) [29,141].…”
Section: Cell Wall Polymersmentioning
confidence: 99%